Social perception of mental illness - Sandu, Mihaela Luminita; Skandalaris , Margarita Alexandra (Technium Social Sciences Journal, 2023)
Mental disorders have been known in all cultures from ancient times to the present day. In the past, most peoples believed that supernatural beings such as deities, spirits and ghosts were responsible for these disorders and resorted to religious rituals to get rid of them. Even today, the ideologies, values and beliefs of each cultural context have a great influence on the manifestation of symptoms of mental illness and the choice of treatment. Perceptions of behaviours that were once considered psychopathological have changed and are now treated differently by psychiatry. People with psychological problems have always been treated with particular suspicion and even fear by society at large. It was common practice to expel them from the community and confine them to an institution. Stigma towards people with mental illness is a long-standing and widespread phenomenon, leading to profound anxiety, disability and negatively affecting quality of life.